Multicultural-based Education on Indonesian Character in Early Childhood Education - Atik Wartini (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2016)
This paper is a field research which examines Multicultural Education based on Indonesian Character on Early Childhood Education. This research is very interesting because the Multicultural Education is assessed on the basis of Indonesian character, while Indonesian must have character as Indonesian people. Furthermore, the Indonesian character needs to be applied early on, especially in early childhood education institutions. In addition, this research is the descriptive one with a qualitative approach. Data were obtained through interviews, observation and documentation. In this paper, there are three questions; first, how is the concept of Multicultural Education based on Indonesian Character according to SALAM?, second, how are the basic principles of learning model development on Multicultural Education based on Indonesian Character in SALAM?, third, how is the implementation of Multicultural Education based on the Indonesian Character in SALAM?. The objectives of this research are: first, to know the concept of Multicultural Education based on Indonesian Character on early childhood in SALAM, second, to know the basic principles of learning model development on Multicultural Education based on Indonesian Character on early childhood education in the school (SALAM), and third, to know the implementation of Multicultural Education based on Indonesian Character on early childhood in SALAM.Tulisan ini merupakan penelitian lapangan yang meneliti Pendidikan berbasis Multikultural pada Karakter Indonesia di Pendidikan Anak Usia Dini. Penelitian ini sangat menarik karena Pendidikan Multikultural dinilai atas dasar karakter Indonesia, sementara Indonesia harus memiliki karakter sebagai orang Indonesia. Selanjutnya, karakter Indonesia harus diterapkan sejak dini, terutama di lembaga pendidikan anak usia dini. Selain itu, penelitian ini adalah deskriptif dengan pendekatan kualitatif. Data diperoleh melalui wawancara, observasi dan dokumentasi. Dalam tulisan ini, ada tiga pertanyaan; pertama, bagaimana konsep Pendidikan berbasis Multikultural pada Karakter Indonesia menurut SALAM ?, kedua, bagaimana prinsip-prinsip dasar pembelajaran pengembangan model Pendidikan berbasis Multikultural Karakter Indonesia di SALAM ?, ketiga, bagaimana pelaksanaan Pendidikan berbasis Multikultural pada Karakter Indonesia di SALAM ?. Tujuan dari penelitian ini adalah: pertama, untuk mengetahui konsep Pendidikan berbasis Multikultural pada Karakter Indonesia pada anak usia dini di SALAM, kedua, untuk mengetahui prinsip-prinsip dasar pengembangan model pembelajaran di Pendidikan berbasis Multikultural pada Karakter Indonesia pada pendidikan anak usia dini di sekolah (SALAM), dan ketiga, untuk mengetahui pelaksanaan Pendidikan berbasis Multikultural pada Karakter Indonesia pada anak usia dini di SALAM.